Detection and Expression of blaKPC-2 and fimH Genes in Klebsiella pneumoniae Clinical Isolates - Sah, Anil Kumar; Sharma, Bikesh Kumar; Bhatt, Manish; Gharti Magar, Milan; Limbu Begha, Neha; Tiwari, Prekshya; Shrestha, Nilima; Lohani, Biraj; Sharma, Subodh; Gajuryal, Sharad Hari; Chandra, Avinash; Pahari, Rabin; et al. (Journal of Nepal Biotechnology Association, 2026)
Klebsiella pneumoniae cause several serious infections, pneumonia, urinary tract infections and bloodstream infections, especially in a immune-compromised patient. There has been rise in antibiotics resistant K. pneumoniae in recent years. This study aimed detection and expression of blaKPC-2 and fimH genes in carbapenemase producing K. pneumoniae that can form biofilms in clinical samples. A total of 608 clinical samples were processed for K. pneumoniae using standard microbiological procedure. Antibiotic resistance was checked using the modified Kirby-Bauer disc diffusion method, and carbapenemase production was tested using a modified carbapenem inactivation method in conjunction with EDTA modified carbapenem inactivation method. In order to detect the presence and expression of resistant genes, bacterial DNA and RNA were extracted.  A total of 30 isolates were positive for K. pneumoniae among which 21 (70%) were multi-drug resistant and 18 (85.71%) were carbapenemase producers in MDR isolates. A total of 14 isolates (66.67%) produced biofilm, of which 6 (28.57%) were strong, 6 (28.57%) were moderate and 2 (9.52%) were weak. Both blaKPC-2 and fimH genes were detected in 19 isolates (90.47%) and were actively expressed in 16 (76.19%). These findings show the blaKPC-2 and fimH genes are common in clinical isolates and are actively being expressed. In conclusion, there is urgent need to control highly resistant K. pneumoniae.